The use of near-infrared angiography in evaluating bowel anastomosis during a gynecologic oncology surgery - Lea A. Moukarzel; Sarah Andres; Oliver Zivanovic (Gynecologic Oncology Reports, 2024)
Reducing anastomotic leak rates after bowel resection is a priority among patients undergoing gynecologic oncology surgery. While near-infrared (NIR) angiography has been investigated in the colorectal literature, more recent work has demonstrated promising results when used in gynecologic cancer surgery. It has been repeatedly shown to be a safe intervention that can offer real time assessment of bowel perfusion, offering the surgeon the opportunity to act on the results in the hopes of decreasing the risk of complications.